1997
DOI: 10.1038/sj.onc.1201233
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of tumor suppressor proteins, p53 and retinoblastoma, by estrogen and antiestrogens in breast cancer cells

Abstract: We have utilized the estrogen receptor (ER)-positive human breast carcinoma cell line, T47D, to determine the role of ER in regulating cell proliferation, the level of expression of p53 and the state of phosphorylation of retinoblastoma protein (pRB) by 17 b-estradiol (E 2 ) and antiestrogens. T47D cells cultured for 7 days proliferated rapidly expressing maximal levels of p53 in medium containing 5% fetal bovine (whole) serum. Exogenously added E 2 had no e ect on either of the above parameters. The antiestro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 22 publications
(28 reference statements)
2
47
0
1
Order By: Relevance
“…32 It is not known why increased exposure to estrogen may lower HCC risk, but experimental data suggest that estrogen can induce expression of certain tumor suppressor genes. 40,41 Otherwise, estradiol is catabolized mainly by hydroxylation reaction. Its 2-hydroxy metabolite can be converted to 2-methoxyestradiol by catechol O-methyltransferase, an enzyme with high levels in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…32 It is not known why increased exposure to estrogen may lower HCC risk, but experimental data suggest that estrogen can induce expression of certain tumor suppressor genes. 40,41 Otherwise, estradiol is catabolized mainly by hydroxylation reaction. Its 2-hydroxy metabolite can be converted to 2-methoxyestradiol by catechol O-methyltransferase, an enzyme with high levels in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…This condition has been shown to reduce basal levels of p53 in estrogen-dependent breast cancer cell lines (Hurd et al, 1997). At protein level, estrogen deprivation resulted in a marked decrease in p53 and Hdm2 expression after long deprivation times.…”
Section: D133p53 Expression Correlates With P53 Protein Levelsmentioning
confidence: 99%
“…The induction of p53 by E 2 occurs prior to hyperphosphorylation of pRB and can be blocked by antiestrogens (Hurd et al, 1995(Hurd et al, , 1997. This suggested that ER acts as a master switch, regulating both a proliferative pathway (cyclin D1 expression-pRB) and in parallel an anti-proliferative pathway involving induction of p53.…”
Section: Introductionmentioning
confidence: 98%
“…Each appears to play a crucial role in apoptosis or programmed cell death, a process thought to be crucial for destroying tumor cells (Evan et al, 1992;Hermeking and Eick, 1994;Lowe et al, 1993Lowe et al, , 1994Hass-Kogan et al, 1995). The proliferative steroid hormone, E 2 has been implicated as an upstream regulator of all three proteins (Hurd et al, 1995(Hurd et al, , 1997Dubick and Shiu, 1988;Altucci et al, 1996;Lukas et al, 1996;Foster and Wimalasena, 1996;Planas-Silva andWeinberg, 1997, Prall et al, 1997), suggesting that E 2 might coordinate their expression in estrogen target tissues.…”
Section: Introductionmentioning
confidence: 99%